Exploring the potentials of volunteered geographic Information as a source for spatial data acquisition - Ariffin I.; Solemon B.; Anwar R.M.; Din M.M.; Azmi N.N. (Institute of Physics Publishing, 2023)
The advancement of technologies nowadays enables participation by nonprofessionals, known as volunteers to participate in producing, sharing and consuming geographic information. Such information, termed as volunteered geographic Information (VGI) has created a new approach of gathering geographic information. This paper discusses the traditional way of acquiring geographic information and potentials of VGI as an information source in GIS applications. We also review four commonly cited applications which rely on volunteers for their geographic information based on five criteria; the geometry type available in the applications, availability of user profile, average number of attributes used in the applications, data type of the information (raster or vector) and the domain the application belongs to. This review serves as a preliminarv study in designing a GIS application used for asset management which aims at exploiting volunteers to produce geographic information related to assets. © Published under licence by IOP Publishing Ltd.